Food Web Functions and Interactions During Spring and Summer in the Arctic Water Inflow Region: Investigated Through Inverse Modeling - Olli, Kalle; Halvorsen, Elisabeth; Vernet, Maria; Lavrentyev, Peter J.; Franzè, Gayantonia; Sanz-Martin, Marina; Paulsen, Maria Lund; Reigstad, Marit (Frontiers in Marine Science, 2019)
We used inverse modelling to reconstruct major planktonic food web carbon flows in the Atlantic Water inflow, east and north of Svalbard during spring (18-25 May) and summer (9-13 August), 2014. The model was based on three intensively sampled stations during both periods, corresponding to early, peak, and decline phases of a Phaeocystis and diatom dominated bloom (May), and flagellates dominated post bloom stages (August). The food web carbon flows were driven by primary production (290 to 2850 mg C m-2 d-1), which was channeled through a network of planktonic compartments, and ultimately respired (180 to 1200 mg C m2 d-1), settled out of the euphotic zone as organic particles (145 to 530 mg C m-2 d-1), or accumulated in the water column in various organic pools. The accumulation of dissolved organic carbon was intense (1070 mg C m-2 d-1) during the early bloom stage, slowed down during the bloom peak (400 mg C m-2 d-1), and remained low during the rest of the season. The heterotrophic bacteria responded swiftly to the massive release of new DOC by high, but decreasing carbon assimilation rates (from 534 to 330 mg C m-2 d-1) in May. The net bacterial production was low during the early and peak bloom (26 to 31 mg C m-2 d-1) but increased in the late and post bloom phases (> 50 mg C m-2 d-1). The heterotrophic nanoflagellates did not respond predictably to the different bloom phases, with relatively modest carbon uptake, 30 to 170 mg C m2 d-1. In contrast, microzooplankton increased food intake from 160 to 380 mg C m2 d-1 during the buildup and decline phases, and highly variable carbon intake 46 to 624 mg C m2 d-1, during post bloom phases. Mesozooplankton had an initially high, but decreasing carbon uptake in May (220 to 48 mg C m-2 d-1), followed by highly variable carbon consumption during the post bloom stages (40 to 190 mg C m-2 d-1). Zooplankton shifted from herbivory (92-97% of total food intake) during the early bloom phase to a herbivorous, detritovorous and carnivorous mixed diet as the season progressed.